1993
DOI: 10.1366/0003702934067351
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved Step-Scan FT-IR Investigations of the Transition from KL to L in the Bacteriorhodopsin Photocycle: Identification of Chromophore Twists by Assigning Hydrogen-Out-Of-Plane (HOOP) Bending Vibrations

Abstract: Sub-microsecond time-resolved step-scan FT-IR spectroscopy is applied to the study of the molecular changes and their dynamics occurring during the KL-L transition of bacteriorhodopsin. The time-resolved difference spectra are compared to the static low-temperature BR → K and BR → L difference spectra. Our data show that the protein part in KL is similar to that in K. However, the chromophore is more relaxed and is differently twisted. A strong hydrogen-out-of-plane (HOOP) mode in KL is assigned to the 15-HOOP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
123
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(139 citation statements)
references
References 44 publications
14
123
2
Order By: Relevance
“…However, C 15 -HOOP signals in K (1-4) and L (6)(7)(8) suggest that the locus of the distortion is at C 15 in both intermediates and, therefore, that the singlebond torsion in K is primarily around the C 14 -C 15 bond and the double-bond torsion in L is primarily around the C 15 ϭN bond. In any case, the results are difficult to reconcile with crystal structures.…”
Section: Resultsmentioning
confidence: 99%
“…However, C 15 -HOOP signals in K (1-4) and L (6)(7)(8) suggest that the locus of the distortion is at C 15 in both intermediates and, therefore, that the singlebond torsion in K is primarily around the C 14 -C 15 bond and the double-bond torsion in L is primarily around the C 15 ϭN bond. In any case, the results are difficult to reconcile with crystal structures.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that this conversion is reversible 2,12,13,18 and that the ratio of the rate constants k LfKL /k KLfL increases with dehydration. 18 To examine the spectral changes with time, our 0-200, 200-400, 400-600, and 600-800 ns FTIR difference spectra are shown directly overlayed in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4] While the resonance Raman technique has dominated this research area thus far, new scientific issues are emerging in the field of chemical and biological reactions that are effectively addressed by transient infrared spectroscopy. One such new theme is the involvement of the surrounding matrix in controlling chemical and biological reaction pathways.…”
Section: Introductionmentioning
confidence: 99%
“…The control of the photo-induced reaction can be done (i) kinetically, by recording the spectrum during a short time after a lightflash or by using time-resolved FTIR difference spectroscopy; (ii) by controlling the sample temperature; (iii) by using chemicals (electron donors and/or electron acceptors, reducing or oxidizing agents) to poise a light-induced reaction intermediate. Time-resolved FTIR spectroscopy involves rapid scan techniques, with 10-25 ms time resolution or step-scan FTIR spectroscopy (Weidlich and Siebert 1993) with time resolution in the ls to ns range (Mezzetti et al 2003;Kötting and Gerwert 2005;Sivakumar et al 2005). In addition, timeresolved IR spectroscopy can be achieved using tunable infrared laser diodes .…”
Section: Light-induced Ftir Difference Spectroscopymentioning
confidence: 99%